x + y = 10 y = x + 8 so, x + (x + 8) = 10 2x + 8 = 10 2x + 8 - 8 = 10 - 8 2x = 2 x = 1 and y = 9 because y = x + 8 y = 1 + 8 y = 9
x-2+4=-8 x+2=-8 x=-10
If x equals 10 and y equals 10, then 9x plus 8y equals 170.
7x + 8 = 10x - 2 ∴ 3x = 10 ∴ x = 10/3
3+10 = 13
(1, 9)
8.
6
x + y = 10 y = x + 8 so, x + (x + 8) = 10 2x + 8 = 10 2x + 8 - 8 = 10 - 8 2x = 2 x = 1 and y = 9 because y = x + 8 y = 1 + 8 y = 9
x + y = 10 y = x + 8 so, x + (x + 8) = 10 2x + 8 = 10 2x + 8 - 8 = 10 - 8 2x = 2 x = 1 and y = 9 because y = x + 8 y = 1 + 8 y = 9
x + 10 = 18 18 - 10 = x 18 -10 = 8 x = 8
x = -8
134
10 x 3 + 8 x 3 30 + 24 54 10 times 3 plus 8 times 3 equals 54.
x-2+4=-8 x+2=-8 x=-10
5x+2=x+10 5x-x=10-2 4x=8 x=2
x= 9